2017
DOI: 10.1177/0268355516686444
|View full text |Cite
|
Sign up to set email alerts
|

Patients and physicians agree only partially in symptoms and clinical findings before and after treatment for varicose veins

Abstract: Objective Quality improvement in surgery has mainly been based on clinical database outcomes. This study compared variables from the patient-reported Aberdeen Varicose Vein Questionnaire with the Danish Clinical Vein Database, in order to reveal agreements and differences in symptoms and clinical findings. Methods In the period January-March 2011, 379 legs in 287 patients treated for varicose veins were registered in the Danish Clinical Vein Database and compared to the Aberdeen Varicose Vein Questionnaire. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Previous studies have independently associated these two aspects with lower quality-of-life scores specific to varicose veins, irrespective of the severity of venous disease. 25 , 32 , 33 , 34 Furthermore, in many circumstances, the age of patients and the severity of comorbidities (such as obesity) may be contraindications to traditional surgical procedures but not to sclerotherapy. Therefore, especially in the public health system, many patients (who already have a lower quality of life due to their clinical characteristics) end up receiving sclerotherapy as their only interventional treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have independently associated these two aspects with lower quality-of-life scores specific to varicose veins, irrespective of the severity of venous disease. 25 , 32 , 33 , 34 Furthermore, in many circumstances, the age of patients and the severity of comorbidities (such as obesity) may be contraindications to traditional surgical procedures but not to sclerotherapy. Therefore, especially in the public health system, many patients (who already have a lower quality of life due to their clinical characteristics) end up receiving sclerotherapy as their only interventional treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were in line with the results of Yun et al (16) in Korea, who used compression stockings for management purposes, while the Klitfod study found that 31% of patients were treated surgically, which was different from the present results. This difference may be related to the nature of the Klitfod study, as it measured the effects of different methods of treatment on relieving the symptoms of patients with VV (17) .…”
Section: Discussionmentioning
confidence: 99%